Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Stuggling with this one: In a simple economic model, time t is set up as a discrete parameter (possibly referring to days or months), while demand $D_{t}$ and supply $S_t$ are described in terms of the price $p_{t-1}$ and $p_{t}$ as follows: since prices influence demand "instantaneously", one puts $D_{t}=\gamma-\delta p_{t}$, but one sets $S_{t}=(p_{t-1}-\alpha)/\beta$ because the production of new commodities consumes time. Assume that all parameters $\alpha, \beta, \gamma, \delta$ are positive, and set $p_{0}=1.$

1) Dervive and solve the difference equation describing economic equilibrium, i.e the situation when $D_{t}=S_{t}$.

$\Rightarrow$ $\gamma-\delta p_{t}= \frac {p_{t-1}-\alpha}{\beta}$ $\Rightarrow$ $\gamma(\beta)-\delta(\beta)\ p_{t}=p_{t-1}-\alpha$ $\Rightarrow$ $p_{t}=\frac {-p_{t-1}+\alpha+\gamma\beta}{-\delta\beta}$

Not sure if this is on the correct lines?

2)Compute the steady states $p^{*}$ and determine a condition on the parameters $\alpha, \beta, \gamma, \delta$ that ensures stabilty of $p^{*}$.

Steady states $p^{*}$:

$p^{*}=\frac {-p^{*}=\alpha+\gamma\beta}{-\delta\beta}$ $\Rightarrow$ $p^{*}-p^{*}(\delta\beta)=\alpha+\gamma\beta$ $\Rightarrow$ $p^{*}=\frac{\alpha+\gamma\beta}{1-\delta\beta}$

Then we want $\alpha, \beta, \gamma, \delta$ that ensures stabilty:

So we call $f(p)= \frac {-p+\alpha+\gamma\beta}{-\delta\beta}$ $\Rightarrow$ $f^\prime= \frac{1}{\delta\beta}$ as being stable $\frac{1}{\delta\beta}<1$ $\Rightarrow$ $1<\delta\beta$.

3) Assume t is measured in days and $p_{t}$ in Pounds sterling. Setting $\alpha=1, \beta=\frac{3}{2}, \gamma=2, \delta=\frac {4}{5}$, how long does it take until $p_{t}$ stays within a penny of $p^{*}$?

Not sure if I'm going down the right lines here, any help will be much appreciated, many thanks in advance.

share|cite|improve this question
up vote 0 down vote accepted

In 1), you have derived the difference equation $$p_t={-p_{t-1}+\alpha+\gamma\beta\over\delta\beta}$$ but you haven't solved it (you also had a minus sign in there where it didn't belong). It is a first-order, linear, constant-coefficient difference equation. Have you learned how to solve that kind of equation?

You're going to need that for part 3), because you're going to need a formula for $p_t$ and then you'll want the value of $t$ that makes $p_t$ differ from $p^*$ by less than a penny.

share|cite|improve this answer
We have kearnt breifly for but in the cases I have we have used $p_{n+1}$ and $p_{n}$. Then say for example using our steady states to obtain the general $p_{n}=\alpha^{n}(p_{0}-p*)+p*$. so struggling how to relate this question to what I have seen, since it asks about the steady states after? – user24930 Mar 1 '12 at 11:34
I don't know what "kearnt breifly for" means. If you are happier with $p_{n+1}$ and $p_n$, can you solve the equation $p_{n+1}=(-p_n+\alpha+\gamma\beta)/\delta\beta$? I don't know what you mean by "it asks about the steady states after." After what? – Gerry Myerson Mar 1 '12 at 11:49
Sorry that was a typo, should of been learnt. So are we using $p_{n}=\alpha^{n}p_{0}+\frac {\alpha ^{n} -1}{\alpha-1} \beta$? – user24930 Mar 1 '12 at 13:19
I don't know what "learnt breifly for" means. I suspect what you have seen is that the general solution to $p_{n+1}=\alpha p_n+\beta$ is $p_n=\alpha^np_0+{\alpha^n-1\over\alpha-1}\beta$. That's what you have to use, but remember that the $\alpha$ and $\beta$ in this last equation are not the $\alpha$ and $\beta$ in your question, a question which also involves $\gamma$ and $\delta$. – Gerry Myerson Mar 1 '12 at 23:55
Think im there now, so in this case our $ \alpha= \frac {-1}{\delta \beta}$ and $\beta= \frac {\beta \gamma +\alpha}{\delta \beta}$. Then consequently from this we can just plug into the general form equation. Really appreciate your help. – user24930 Mar 3 '12 at 14:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.